Pembelajaran Berbasis Inkuiri dengan Model The 5 E Learning Cycle dapat Meningkatkan Keaktifan Belajar dan Hasil Belajar Siswa - Rudi Purnomo (Kayon Media, 2019)
Learning inquiry with The 5E Learning Cycle use increase active and learning outcomes. Indicates that the students tend to be passive and less active. Students’ activeness is determined from the data on the courage to ask question, to express opinion, and to argue the idea during learning. The learning result includes some aspects such as learning skill, psychomotoric skill, and cognitive skill, which all of them come from the evaluation (test) over students. Data collection methods are the writing test for students, the assessment of learning skill and psychomotoric skill from observation sheet, and questionnairePembelajaran inkuiri dengan model The 5E Learning Cycle dapat digunakan meningkatkan keaktifan belajar dan hasil belajar siswa. Tujuan dari pembelajaran ini agar siswa tidak cenderung pasif dan kurang aktif dalam belajar, juga siswa tidak mempunyai kecenderungan pada hafalan-hafalan saja. Keaktifan siswa diperoleh dari data keterlibatan mereka dalam keberanian bertanya, keberanian mengemukakan pendapat, dan keberanian mempertanyakan gagasan saat pembelajaran. Hasil belajar meliputi aspek keterampilan belajar, aspek psikomotorik dan aspek kognitif yang dipeoleh dari evaluasi (tes) kepada siswa.